(3GdEMUGA (B1 / s - (3bQjSj, jGSjfs; (3LGeYI GdLRGFQ(B3: (3cdjI GdYdhe GdEbJUGOjI, GdYdhe GdJLGQjI hYdhe GdJSjjQs ((3GdLRGFQs (3LGeYI GdLRGFQ(B3: (3cdjI GdYdhe GdEbJUGOjI, GdYdhe GdJLGQjI hYdhe GdJSjjQs, 2021)
(3eaGgje CSGSjI aj Yde GdGMUGA , GdYQV GdLOhdj ddHjGfGJ GdGMUGFjI , GdYQV GdHjGfj ddHjGfGJ GdGMUGFjI , ebGjjS GdfRYI GdeQcRjI , ebGjjS GdJTJJ , ebGjjS GdTcd s
(3eQGLY U(B.70s
Keywords: (3GdGMUGAs